MAKNA CINTA DALAM SASTRA INDONESIA LOMBOK - HD, Dharma Satrya; Nurmayani, Eva; Yuliatin, Riyana Rizki (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This article discusses the meaning of love in Lombok Indonesian literature. The meaning of love is discussed in the context of romanticism. This article tries to answer what is the meaning of love if it tends to the poles of the ideal world or to the poles of the real world. This article describes the conceptualization of love in Lombok Indonesian literature. To explain this problem, this article uses representation theory with semiotic analysis method. The theory assumes that literary works are a representation of reality, not a presentation of reality. Literary work as a sign which is the unity between a signifier and signified, both at the level of language and  myth. This article shows that the tendency of love to the poles of ideal world, interprets love as loyalty and responsibility. While the tendency of love to the poles of the real world, interpreting love as liberating feeling. The tendency of the meaning of love, which reject both poles, constructs the meaning of love as a blessing for other, not as suffering for other. The tendency to unite the poles, the ideal and the real, constructs love as of act of elopement, merarik.